Tinjauan Yuridis Perjanjian Sewa Guna Usaha Dengan Hak Opsi (Financial Lease) Dalam Perspektif Hukum Positif Indonesia - Sulivan, Robby; Widjaja, Gunawan; Rusli, Hardijan (LAW REVIEW, 2004)
Nowadays, business world competition becomes fiercer. With such a competition, high efficiency is needed to face it. In conducting its activities, a company will meet various problems, such as capital goods fulfilment. In acquiring the capital goods, huge amount of money is required certainly. To solve the problem, financial lease transaction applied.  Financial lease is company financing activity in terms of capital goods supply in order to be used by the company for a certain period, based on periodical payments, accompanied by option right (optie) for the company to purchase related capital goods or to extend the leasing period based on agreed left over value. Leasing as a kind of financing activities has been recognized in Indonesia since 1974, marked by Multiple Agreement Letter  about Leasing Business Permission among Indonesian Minister of Finance, Minister of Industry, and Minister of Trade; Number: Kep-122/MK/IV/2/1974, Number: 32/M/SK/2/I974, and Number: 30/Kpb/I/74. Based on a study on analysis unit in this writing, the author will describe financial lease agreement law position within Indonesian positive law perspective. Also in this writing, rights and obligations of all involved parties  in financial lease agreement will be discussed.